Analysis of Bank Financial Performance with Financial Ratio: Analysis of CAR, NPF, BOPO, FDR and ROA in Indonesian Sharia Commercial Banks for the Period 2018-2022 - Samsi, Nur; Elfa Kolina, Hepy Octalia; Sukoco, Agus (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: Analyze the Influence of CAR, NPF, BOPO and FDR on the Profitability (ROA) of Indonesian Sharia Commercial Banks registered with the Financial Services Authority (OJK) during the 2018-2022 period. Design/methodology/approach: This study uses a quantitative approach and uses secondary data with a sample of 65 data obtained from 13 Sharia Commercial Banks with a time series of 2018-2022. Findings: CAR partially had a positive and significant effect on ROA, NPF partially had a positive and insignificant effect on ROA, BOPO partially had a negative and significant effect on ROA, FDR partially had a positive and insignificant effect on ROA, and CAR, NPF, BOPO, and FDR simultaneously had a positive and significant effect on ROA in Sharia Commercial Banks in Indonesia for the period 2018-2022. Paper type: Research paper